Decolourization of congo red synthetic dyes by dark septate endophytes. Issue 1 (December 2021) - Melati, I; Rahayu, G; Surono; Effendi, H; Henny, C
Abstract: The use of fungi is known to be an eco-friendly and cost-competitive approach to degrade synthetic dyes such as Congo Red (CR) in industrial effluents. This research aimed to evaluate the potential of dark septate endophytes (DSE) fungi in decolourizing CR synthetic dyes. Two DSE strains, namely CPP and KSP, were studied to decolourize 50 mgL −1 CR based on the capability to produce the ligninolytic enzyme, dye decolourization efficiency, decolourization index, and fungal dry biomass weight after 7 and 14 days of incubation. CR decolourization was monitored spectrophotometry at 495 nm. The result indicated that CPP and KSP were successfully decolourized CR dye up to 97.00% and 85.00%, respectively, with decolourization index of 1.37 and 1.36 within 14 days. There is no significant difference in DSE growth with and without the addition of CR dye. In addition, these two DSE fungi (CPP and KSP) are able to produce ligninolytic enzymes. The results indicated that the DSE are potential to be used as decolourization agents for azo synthetic dyes. This is the first report on the ability of DSE to decolourize azo synthetic dyes.